Rewitalizacja terenów poeksploatacyjnych na obszarze miasta Konina = Revitalisation of post-mining resions in the area of the town of Konin - Gilewska, Mirosława; Otremba, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study is concerned with the process of revitalisation of post-mining regions of Niesłusz and Gosławice brown coal open-cast mines. These areas are situated in the northern part of the town of Konin and occupy approximately 15,6% of its area. In 1960s and 1970s, they underwent restoration, mainly in the form of forest or agricultural reclamation.
Keywords: odkrywka węgla brunatnego; zwałowisko; rekultywacja leśna; rekultywacja rolnicza; rewitalizacja przyrodnicza; forest recultivation; agricultural recultivation; natural recultivation